International Evidence on the Value of Product and Geographic Diversity - Laeven, Luc (World Bank, Washington, DC, 2014)
The author examines the effect of product and geographic diversification on firm value for a sample of 1,914 corporations in 18 countries. His results indicate that both product and geographic diversification destroy value at high levels of diversification, suggesting that agency and influence costs arising from the increased complexity outweigh the benefits of diversification at high levels. Geographic diversification is valuable at low levels, however. The author finds that insider ownership is associated with less diversification, across both product and geographic segments, suggesting that insiders view corporate diversification as value destroying.